A 56-Year-Old Man with an Unusual Projectile Trajectory of Gunshot Wound at Head and Neck Region: A Rare Case Report - Zulfikar, Welli; Moh. Habib (HM Publisher, 2024)
Background: Gunshot injuries to the neck are linked to a substantial risk of high mortality and morbidity due to the presence of critical vascular and vital structures. However, there are rare instances where a bullet trajectory through the neck region avoids damaging these vital structures. In this context, we report a specific case involving a 56-year-old male who presented to the emergency department with a gunshot wound to the right maxilla through the left anterior neck region. Case presentation: During the examination, a hematoma was observed in the left neck without an apparent entrance wound. The occurrence of a bullet injury to the neck without affecting any vital structures is exceptionally uncommon. Effectively managing patients with high-velocity penetrating injuries to the head and neck entails prioritizing tasks such as securing the airway, controlling hemorrhage, and promptly addressing any residual traumatic deformities for optimal outcomes. The presented case involves a gunshot injury to the head and neck, and a comprehensive review of the literature is provided. Conclusion: Gunshot injuries to the head and neck are complex and serious, demanding swift and thorough medical attention. The case emphasizes the significance of post-surgery monitoring for potential complications, contributing valuable insights to the ongoing discourse on managing such injuries.